The Significance of Introducing Culture in EFL Instruction - Noor Malihah (Register Journal, 2008)
EFL students many times made mistakes in using the English expressions and led to misinterpretations or even acceptable message of their utterances. This is due to their lack of cultural awareness or their understanding towards L2 culture. Therefore, EFL teachers should think of how to give position to the L1 and L2 culture in their teaching and learning process of EFL instructions.To solve the problems, there are some approaches used to introduce the target language culture, by knowing the obstacles that the learners frequently made. Keywords: EFL; Cultural Awareness; Approaches; Obstacles